Influência da composição da paisagem sobre o rendimento da pesca no reservatório da usina hidrelétrica de Curuá-una, Santarém-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2013)
The landscape ecology uses indicators that relate ecological and socioeconomic systems , providing the basis for planning and territorial management , emphasizing the natural landscapes , and thus contributing to the conservation of biodiversity . In the Amazon , fishing is an activity very significant for its population that has a narrow grating with the capture areas . In this context , is the coastal living on the shores of the dam Curuá- Una . This work was developed in order to evaluate the effect of composition and landscape structure on income fishing in the reservoir of the dam , as well as to characterize the dynamics of the fishing communities affected by the reservoir of the dam with different compositions landscape of fisheries and its surroundings. Therefore , the process of data collection occurred at two levels : initially the yield was quantified fishing ( Catch Per Unit Effort ) , obtained by means of the estimates of local fishermen during four field trips covering the rainy season and the dry season and then quantifying the classes that make up the landscape around the reservoir of Curuá -Una , obtained through a series of computational algorithms adopted in geographic information systems . Thus, it can be observed that in the rainy season , areas with higher forest on the banks showed higher yield fishing . However , the decrease in the amount of vegetation cover ( Fragments not forested ) negatively affected the fishery yield . The amount of forest around the reservoir Curuá- Una has a positive effect on yield and fishing in areas with less forest, evidenced lower incomes fishing . The composition of the landscapes around 5km reservoir Curuá -Una affects the performance of the fishing communities. Especially in the rainy season , when the amount of rainfall determines greater entrainment of sediment into water bodies.
Keywords: Ecologia de paisagem; rendimento pesqueiro; Deflorestamento; Unidade de esforço; CNPQ::CIÊNCIAS EXATAS E DA TERRA; CONSERVAÇÃO E MANEJO DA BIODIVERSIDADE NA AMAZÔNIA